بحث تطبيقي في الهيئة العامة للضرائب في العراق: Applied research in the General Tax Authority in Iraq (Journal of Accounting and Financial Studies ( JAFS ), 2024)
The research aims to explain the role of the Insurance Bureau in improving tax accounting procedures as a supervisory and monitoring body for the insurance sector in Iraq and a support for the financial authority by applying a set of controls, rules and systems to insurance companies in accordance with the Insurance Business Regulatory Law No. 10 of 2005, and because of this body’s major role. In the transparency and credibility of the inputs to the tax accounting process, which are the financial statements and reports of the 34 private insurance companies, local insurance companies, branches of foreign insurance companies, 22 insurance brokerage companies, and a large number of insurance agents and insurance service providers, so that they are credible and thus limit cases of tax evasion, which leads to an increase in the outcome. The tax and its impact on state revenues and enabling the government to perform its tasks and implement its programs.The research reached a set of conclusions, the most important of which are: weak direct cooperation and coordination between the Insurance Bureau and the financial authority represented by the General Authority for Taxes, and a lack of knowledge of the problems of tax accounting for private insurance companies in a way that preserves the rights of society on the one hand and the rights of the state on the other hand. The research recommended a set of recommendations, the most important of which are: the need for the Insurance Bureau to conduct field inspections of private insurance companies, review the accounting records and sections, prepare reports resulting from the field inspection, and provide the General Authority for Taxes with copies of these reports and the results of field tours to solve the problems of tax accounting for these companies, and direct coordination between the Bureau Insurance and financial authority to identify the problems that this vital sector suffers from.